2020
DOI: 10.1016/j.radonc.2020.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial on reduction of radiotherapy dose to the elective neck in head and neck squamous cell carcinoma; update of the long-term tumor outcome

Abstract: Background and purpose: A multicenter prospective randomized controlled trial was performed to investigate whether dose reduction to the elective nodal volume (PTVelect) in head and neck carcinoma reduces radiation-induced dysphagia, primary endpoint, without compromising tumor control, secondary endpoint. Here, we report on the long-term follow-up of the secondary endpoint (NCT01812486). Materials and methods: Two hundred patients treated with primary (chemo)radiotherapy (RT) were randomized (1:1) between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Furthermore, in a randomized study consisting of 200 HNSCC patients comparing ENI of 40 Gy versus 50 Gy, no statistically significant differences in treatment outcome were observed. Although the study was underpowered to undoubtedly detect non‐inferiority, it appears safe to reduce the dose of ENI to subclinical disease 69 . This is in accordance with the fact that patients historically received 50 Gy in 25 fractions specified at the maximum dose ( D max ) to the low neck with Co‐60 and thus, the LNs received approximately 80%–85% of the given dose.…”
Section: Treatment Considerationsmentioning
confidence: 68%
See 1 more Smart Citation
“…Furthermore, in a randomized study consisting of 200 HNSCC patients comparing ENI of 40 Gy versus 50 Gy, no statistically significant differences in treatment outcome were observed. Although the study was underpowered to undoubtedly detect non‐inferiority, it appears safe to reduce the dose of ENI to subclinical disease 69 . This is in accordance with the fact that patients historically received 50 Gy in 25 fractions specified at the maximum dose ( D max ) to the low neck with Co‐60 and thus, the LNs received approximately 80%–85% of the given dose.…”
Section: Treatment Considerationsmentioning
confidence: 68%
“…Clinical studies in HNSCC using lower ENI to the neck of less than 50 Gy have been reported 68,69 . Salama et al compared three different dose schemes of ENI (45, 39, and 36 Gy) in treating patients with head and neck cancer after induction chemotherapy in a multi‐institutional phase II trial and found that locoregional control and OS were not different among the groups 68 .…”
Section: Treatment Considerationsmentioning
confidence: 99%
“…Advanced tumour stage (T3-T4), oropharyngeal and nasopharyngeal tumour site, primary and bilateral neck irradiation, weight loss at baseline, and treatment modality (accelerated RT or CCRT) were identified as independent factors predicting swallowing dysfunction. In Belgium, such studies are focussing on reduction of the elective dose and on volume individualisation of the prophylactic nodal target irradiated zone using the identification of the sentinel node [ 33 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…(25)(26)(27)(28)(29)(30)(31). Subsequently, several studies are currently focusing on reducing the elective radiation dose and the irradiated volume in order to decrease acute and late swallowing dysfunction (32)(33)(34)(35). Langendijk et al developed a predictive model to identify patients at high risk of radio-induced dysphagia (14).…”
Section: Discussionmentioning
confidence: 99%
“…Advanced tumour stage (T3-T4), oropharyngeal and nasopharyngeal tumour site, primary and bilateral neck irradiation, weight loss at baseline, and treatment modality (accelerated RT or CCRT) were identi ed as independent factors predicting swallowing dysfunction. In Belgium, such studies are focussing on reduction of the elective dose and on volume individualisation of the prophylactic nodal target irradiated zone using the identi cation of the sentinel node (33,35).…”
Section: Discussionmentioning
confidence: 99%